The exposure in ovo of embryos belonging to Amazonian turtle species Podocnemis expansa (Testudines) to commercial glyphosate and fipronil formulations impairs their growth and changes their skeletal development - Mendonça, Juliana dos Santos [UNESP] (2022)
Pesticides are widely used in agricultural production; moreover, they can have direct and indirect effect on both flora and fauna. Aquatic organisms, among other animals, including reptiles, are mainly susceptible to contamination effects. Accordingly, the aim of the present study is to test the hypothesis that the incubation of Podocnemis expansa eggs in substrate added with glyphosate and fipronil formulations changes their viability, interferes with their growth and induces bone alterations. Eggs collected in natural environment were artificially incubated in sand moistened with water added with glyphosate Atar 48, at concentrations of 65 or 6500 μg/L (groups G1 and G2, respectively), and with fipronil Regent 800 WG at 4 or 400 μg/L (groups F1 and F2, respectively) or, yet, with the combination of 65 μg/L glyphosate and 4 μg/L fipronil, or with 6500 μg/L glyphosate and 400 μg/L fipronil (groups GF1 and GF2, respectively). The level of exposure to the herein assessed pesticides was quantified at the end of the incubation period; it was done by dosing its concentration in eggshells. Eggs exposed to the tested pesticides did not have their viability affected by it; however, all embryos exposed to the tested pesticides showed lowered body mass at hatch, as well as impaired development. In addition, bone malformation in the scleral ossicular ring was observed in individuals in groups F1, F2 and GF1. Pesticides accumulated in eggshells at concentrations related to exposure level. Thus, the recorded results have evidenced some remarkably relevant, and previously unknown, impacts associated with the exposure of a species listed as lower risk/conservation dependent, which spends most of its life in the water, to two widely used pesticides, at a very sensitive stage of its life, namely: egg incubation on land.